Second language learners’ vocabulary expansion is associated with improved second language vowel intelligibility - Bundgaard-Nielsen, R.; Best, C.; Kroos, Christian; Tyler, M. (Cambridge University Press, 2012)
This paper tests the predictions of the vocabulary-tuning model of second language (L2) rephonologization in the domain of L2 segmental production. This model proposes a facilitating effect of adults’ L2 vocabulary expansion on L2 perception and production and suggests that early improvements in L2 segmental production may be positively associated with an expanding L2 vocabulary. The model was tested in a study of the L2 vowel intelligibility of adult Japanese learners of Australian English, who differed only in the size of their L2 vocabularies. The results support the predicted association between L2 vocabulary size and L2 vowel intelligibility and the prediction that early-phase L2 vocabulary expansion leads to improved L2 production.